L’autre Allemagne dans l'Allemagne unifiée. Réflexions sur l'unification allemande (Note) - Paraïso, Jean-Yves (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1997)
The serious economic problems that the unified Germany has to face — as must other industrialized countries - cannot by themselves account for the growing disenchantment that is perceptible in the New Länder, where the utopian dreams of the fall of 1989 have been steadily unravelling. Why is it that the people of the GDR, who had pushed aside the lethargy of politicians in order to impose a speedy unification of the two German states, now seem to be adopting a radical attitude of defiance towards the federal government ? The author postulates that, in implementing the unification process, people overestimated the capability of the West German federal model to integrate the territories of the GDR and underestimated the permanence of the political consciousness specific to East German citizens, the weight of their historical experience, and their profound yearning to assume their destiny within a unified Germany. Had an autonomous East German chamber been created, with a time-limited mandate, it might have been possible to give meaning to the collective quest for identity now being expressed in the New Länder, a quest which for the time being, and in the absence of any alternative, finds an outlet in a party incarnating the region's specificity - the PDS.